Examination of the Unmanned Aerial Vehicle - Setlak Lucjan; Kowalik Rafał (ITM Web of Conferences, 2019)
The contemporary interdisciplinary field of knowledge, which is the robotics used in unmanned aerial vehicles, is developing very dynamically. In view of the above, the authors of this paper have set themselves the following thesis: it is possible to build a flying mobile robot based on a controller with low computing power and a simple PID controller, and in this respect they undertook to prove it. The examined object in real experiments was the Quadrocopter. The article discusses the tasks implemented during the design and practical implementation of a remotely controlled flying unit. First, a mathematical model describing the dynamics of the UAV movement was defined. Then, electronic components were selected to allow the quadrocopter to fly. The board has a central unit in the form of the ATmega644PA microcontroller. In the following, the process of programming subsequent elements that make up the quadrocopter control program was carried out. The control system for stabilizing the machine requires information about the location of the quadrocopter in space. This is accomplished by a measurement module containing an accelerometer and a gyroscope. In addition, the quadrocopter needs information about the potential operator's commands. In the final part of the article, based on the analysis of the research subject, the mathematical model created and the necessary simulation tests carried out in this area, practical conclusions were presented.